2001
DOI: 10.1002/cncr.10177
|View full text |Cite
|
Sign up to set email alerts
|

Selective upregulation of vascular endothelial growth factor receptors neuropilin‐1 and ‐2 in human neuroblastoma

Abstract: BACKGROUND Recent studies show that vascular endothelial growth factor (VEGF) and its receptors Flt‐1 and KDR, and a series of other angiogenic molecules, are upregulated in advanced but not low stage human neuroblastoma. Neuropilin‐1 and 2 (NRP) are novel specific receptors of VEGF165, whose role is unknown in human neuroblastoma. METHODS Tissue biopsies of 37 children with Stage I‐IV neuroblastoma were obtained, as well as biopsies of 7 normal adrenals as controls. The mRNA expression of VEGF165 and its rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 20 publications
1
62
0
1
Order By: Relevance
“…Np-1 and Np-2 are up-regulated in the endothelial cells of human neuroblastomas (42), and their concomitant overexpres- sion is associated with increased vascularity and poor prognosis in non-small cell lung cancer (43). Furthermore, Np-1 promotes the angiogenic process during wound healing (44), whereas Np-2 is expressed in pancreatic endocrine islet cells and in endocrine tumors in the gastrointestinal tract (45).…”
Section: Discussionmentioning
confidence: 99%
“…Np-1 and Np-2 are up-regulated in the endothelial cells of human neuroblastomas (42), and their concomitant overexpres- sion is associated with increased vascularity and poor prognosis in non-small cell lung cancer (43). Furthermore, Np-1 promotes the angiogenic process during wound healing (44), whereas Np-2 is expressed in pancreatic endocrine islet cells and in endocrine tumors in the gastrointestinal tract (45).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, VEGF was found to bind to tumour cells which did not express VEGFR-1 or VEGFR-2 [38] and it was subsequently found that these cells express NRPs. NRP-1 expression was observed in some tumours and originally thought to be exclusively expressed by the tumour endothelium but more recently NRP-1 expression was identified on tumour cells such as the MDA-MB-231 breast tumour cells, human astrocytomas, neuroblastoma, lung, pancreatic, gastric tumour cells and colon cancer cells [42][43][44][45][46][47][48][49]. Neuropilin-2 (NRP-2) can also bind VEGF, but like NRP-1 lacks a cytoplasmic signaling domain.…”
Section: Vegf Receptorsmentioning
confidence: 99%
“…In addition, it has been shown that when administered with a frequent, low-dose schedule, certain chemotherapeutic drugs can have potent antiendothelial cell activity (9,10). Conversely, evidence is accumulating that VEGF blockade, although traditionally presumed to exert direct activity only against the tumor endothelium, may also have direct antitumor effects against certain malignancies (11).…”
mentioning
confidence: 99%